A motivation model for interaction between parent and child based on the need for relatedness - Ogino, Masaki; Nishikawa, Akihiko; Asada, Minoru (Frontiers in Psychology, 2013)
In communication between parents and children, various kinds of intrinsic and extrinsic motivations affect the emotions that encourage actions to promote more interactions. This paper presents a motivation model for the interaction between an infant and a caregiver which models relatedness, one of the most important basic psychological needs, as a variable that increases with experiences of emotion sharing. Relatedness is not only an important factor of pleasure but also a meta-factor which affects other factors such as stress and emotion mirroring. In the simulation experiment, two agents, each of which has the proposed motivation model, show emotional communication depending on the relatedness level that is similar to actual human communication. Especially, the proposed model can reproduce a finding described by the "still-face paradigm", in which an infant shows unpleasant emotion when a caregiver suddenly stops facial expressions. The proposed model is implemented in an artificial agent with a recognition system for gestures and facial expressions. The baby-like agent successfully interacts with an actual human and shows reactions comparable to the "still-face paradigm".